Screening eye diseases in babies: an italian experience on 5000 healthy, consecutive newborns - Roberto Perilli; Modesto Lanci; Antonino Romanzo; Laura Sabatini; Paola Fusilli (Istituto Superiore di Sanità, 2015)
INTRODUCTION: Visual performance of eyes with congenital pathologies is conditioned by an early diagnosis. Families having problems in accessing health services risk to delay or miss both an early diagnosis and an early treatment and amblyopia (lazy eye) prevention. METHODS: In our hospital, all full-term, healthy newborns are thoroughly examined by an ophthalmologist in the maternal ward, 1 to 3 days after birth. RESULTS: Among the first 5000 newborns examined, a high incidence of congenital pathologies compared to international literature was reported, with differences between Caucasians and non-Caucasians. CONCLUSION: Performing an early in-hospital thorough eye examination in all newborns as a screening would be an effective way to miss none and to start an early and effective pathway of disease treatment.